Praktik Fraud Accounting dan Benang Kusut Pemicu Kebiasaan Game On Paper: Studi Fenomenologi pada Organisasi Sektor Publik - Dewi Putri; Ema Fritania; Robinsen Kwe; Rafles Ginting (Ikatan Cendekiawan Muda Akuntansi (ICMA), 2024)
The purpose of this research is to analyze and evaluate the factors that trigger fraud accounting practices in the form of game on paper habits. This type of research uses qualitative narrative using the main data through observation, in-depth interviews and documentary research, this research describes what triggers the habit of gaming on paper. The purpose of this study is to analyze the triggers of fraud accounting practices in the form of game on paper habits. Based on the results of research and discussion related to the disclosure of game on paper fraud culture, it can be concluded that this research provides an overview of the events experienced regarding the tradition of manipulating notes or evidence of financial transactions so that it becomes a habit and can be found in organizations. Internal controls that need to be implemented to minimize fraud are forming a special audit team for student organizations, conducting regular internal audits, conducting socialization related to harassment from fraud accounting, and designing a validation system for proof of transaction activities in student organizations.